Insan Kamil dalam Perspektif Syaikh Abd al-Karim al-Jili - Kiki Muhamad Hakiki (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
The study of Insan Kamil (the perfect man) is one of the important themes in the world of Sufism. One of the evidence that could be peculiarly noted is the written books of Sufism. Of those books that specifically concern into this theme is Abd al-Karim al-Jili with his prominent work Al-Insan Al-Kamil fi Ma'rifat al-Awakhir wa al-Awa'il. In his text, the outlook of Insan Kamil is different from the other studies, such as in the works of Ibn 'Arabi, Al-Hallaj, Al-Suhrawardi, and At-Tirmidhi. Although Al-Jili is not a pioneer of the study of Insan Kamil, his concept, which is different from its predecessors, is more comprehensive. As a comparative study of predecessor notion, the work of Ibn 'Arabi is taken as an example of Al-Jili modification. Based on the simple and brief readings, it can be found that the concept of Insan Kamil initiated by al-Jili is a theological notion, and Insan Kamil initiated by Ibn 'Arabi philosophical patterned.